Israeli apartheid : a beginner's guide - White, Ben, 1983- (PlutoPress, 2014)
Since its release in 2009 Israeli Apartheid: A Beginner's Guide has become an essential primer for undergraduate students and activists getting to grips with the Palestine/Israel conflict for the first time. Ben White skilfully distills the work of academics and experts into a highly accessible introduction. This new updated and expanded edition includes information on the Israeli blockade and attacks on the Gaza Strip since 2008, new policies targeting Palestinian citizens of Israel and the growth of the global Boycott Divestment Sanctions campaign. Packed with vital information, quotations and resources, Israeli Apartheid never loses the human touch. The book is rooted in the author's extensive personal experience in Palestine and includes testimonies by Palestinians describing how Israeli apartheid affects their daily lives. -- Provided by publisher.